Pengaruh Rasio Keuangan Dalam Memprediksi Perubahan Laba Pada Industri Farmasi - Torano, Nety (Journal Of Human And Education (JAHE), 2025)
This study aims to evaluate the effect of the current ratio, WCTA, NPM, ROE, and ROA on profit changes. The approach used is multiple linear regression with a research sample consisting of 11 pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) during the 2019 to 2022 period. The findings indicate that, partially, the current ratio, WCTA, ROA, and ROE have an impact on profit changes, while the NPM variable does not have a significant effect. Simultaneously, the variables current ratio, WCTA, NPM, ROA, and ROE collectively influence profit changes.